Branchial cleft cyst: A case report and literature review - R Swarna Lakshmi; G Nandhini; V S Jayant; K Rajkumar (Wolters Kluwer Medknow Publications, 2017)
Branchial cleft cysts are the most common congenital neck masses which originate from remnants of the branchial arches or branchial pouches. The lesion presents as an asymptomatic circumscribed movable mass on the anterior border of the sternocleidomastoid muscle. The dentist should be aware of this entity, because it can be easily confused with an odontogenic infection or parotid pathology, especially, if it develops high up in the neck. In this article, we report a case of infected branchial cyst in the left side of the neck region along with its literature review.